Antioxidant Enzyme Inhibitor Role of Phosphine Metal Complexes in Lung and Leukemia Cell Lines. (28th December 2014) - Saygıdeğer Demir, Burcu; Keleş, Tuğba; Serindağ, Osman
Abstract : Phosphine metal complexes have been recently evaluated in the field of cancer therapy. In this research, the cytotoxic effects of some metal phosphines{ [PdCl2 ((CH2 OH)2 PCH2 )2 NCH3 ] (C1), [RuCl2 (((CH2 OH)2 PCH2 )2 NCH3 )2 ] (C2), [PtCl2 ((Ph2 PCH2 )2 NCH3 )(timin)2 ] (C3)} on K562 (human myelogenous leukemia cell line) and A549 (adenocarcinomic human alveolar basal epithelial cells) cells were investigated using the MTT test. C1 and C2 are water-soluble metal complexes, which may have some advantages in in vitro and in vivo studies. The effects of the above-mentioned metal complexes on thioredoxin reductase (TrxR) (EC: 1.8.1.9), glutathione peroxidase (GPx) (EC: 1.11.1.9), and catalase (Cat) (EC: 1.11.1.6) enzymes were also tested. The results of this research showed that all three metal complexes indicated dose-dependent cytotoxicity on A549 and K562 cell lines and that the complexes inhibited different percentages of the TrxR, GPx, and Cat enzymes of these tumor cells.